PENGEMBANGAN STRATEGI PEMASARAN LAYANAN LAPAROSCOPY DI RUMAH SAKIT ISLAM JAKARTA PONDOK KOPI - Vannisa Fandyar Maulidhika; Sutopo Patria Jati; Anneke Suparwati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The development of health industry today continuously has a rapid growth, one of which is hospital. Jakarta Islamic Hospital Pondok Kopi is one of the private hospitals in Special Capital Region of Jakarta which has a new service that could be a solution for people who needs an efficient and fast health services, which is Laparoscopic surgery. However, today Laparoscopy utility services still tend to be low. The lack of utility services was the consequence of the marketing activities run by the hospital has not maximal yet. The purpose of this study is to determine the development of marketing strategy for Laparoscopy services in Jakarta Islamic Hospital Pondok Kopi. The type of study used in this study is the Exploratory Research with qualitative methods. The data are collected throughin-depth interview and secondary data. The key informants amounted is 4 people and triangulation informants amounted is 2 people. Based on the research, revealed that Jakarta Islamic Hospital Pondok Kopi is located in the first quadrant of the SWOT diagram, meaning the hospital is in a favorable position, they had an opportunity and power so that they could take advantage of the opportunities before the eyes. The strategies for these circumstances is to support aggressive growth policy (growth strategy). The strategies that can be applied is to increase the role and function of marketing , to maximize the activity of marketing conduct an evaluation of the marketing activities undertaken , increasing the types of surgical procedures that can be treated with laparoscopy , improve service quality , establish cooperation with commercial insurance and the company , and establish relationships with the community certain communities. The suggestions of this research are the hospital should improve the quality of services and maximize the marketing activities.